1973
DOI: 10.1364/ao.12.000048
|View full text |Cite
|
Sign up to set email alerts
|

Kramers-Kronig Analysis of Relative Reflectance Spectra Measured at an Oblique Angle

Abstract: Relative specular reflectance R is defined as R = R(s)/R(w), where R(s) and R(w) are absolute reflectances of a sample material s and a material w for which the index of refraction n(w) and the extinction coefficient k(w) are known quantities. An algorithm was developed for computing n(s)and k(s) from the sample's R spectrum measured for radiant flux polarized perpendicular to the plane of incidence and reflected at oblique angle theta. Kramers-Kronig analysis of the R spectrum provides DeltaPhi the difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1975
1975
1997
1997

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The relation permits both n and K to be found from a numerical integration of the measured reflectivity. The technique has been extended by Hale et al [ 1973] to include measurements of relative reflectance and reflectance at nonnormal incidence. Indeed, the Kramers-Kronig technique is quite general, and for example, a relation similar to (4b) can be written between n and K so that if K is known, n can be found.…”
Section: [T/(1 -R )•']/Ln [T/( 1 -R )•] Typical Fractional Errors Tementioning
confidence: 99%
“…The relation permits both n and K to be found from a numerical integration of the measured reflectivity. The technique has been extended by Hale et al [ 1973] to include measurements of relative reflectance and reflectance at nonnormal incidence. Indeed, the Kramers-Kronig technique is quite general, and for example, a relation similar to (4b) can be written between n and K so that if K is known, n can be found.…”
Section: [T/(1 -R )•']/Ln [T/( 1 -R )•] Typical Fractional Errors Tementioning
confidence: 99%
“…It was found that the relative reflectance spectra for the X and Z directions contained a hump which centered for both at approximately 2600 cm 4 . The anomalous feature in the X spectrum was quite distinct and extended from roughly 2300 cm 1 to 2900 cm I .…”
mentioning
confidence: 99%
“…Hale and Querry (1973) previously published values of the complex refractive index of water in the 200 mm to 200 pm wavelength range. Their investigation was based on a KK analysis of a k spectrum for water compiled from about 80 papers in the scientific literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of reflection in a medium other than vacuum [81][82][83][84] or at nonnormal incidence [81,[84][85][86], the dispersion relations must be modified to account for more complex terms in the phase shift [46]. Dispersion relations [89] and sum rules [90] for the real and imaginary parts of the ellipsometric function have been developed. While this more complex situation has led to discussions of the validity of dispersion analysis [87,88], sum rules have not been investigated for these more general cases except in the case of ellipsometry.…”
mentioning
confidence: 99%